2012
DOI: 10.1590/s1678-86212012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Análise hierárquica para escolha entre agregado natural e areia de britagem de rocha para confecção de argamassas de revestimento

Abstract: Muitas vezes as tomadas de decisão na indústria da construção são complexas, pois envolvem muitas variáveis, sendo trabalhoso agrupá-las e realizar uma avaliação global do problema. O método de análise hierárquica (AHP) é uma ferramenta que auxilia na tomada de decisão em problemas de engenharia, nos quais diversos fatores devem ser levados em conta na escolha de métodos, produtos ou materiais. O objetivo principal deste artigo é mostrar a forma de aplicação do método de análise hierárquica para sistematizar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…Mortars with treated fibers exhibit a gradual decrease in the air incorporated concentration as the fiber incorporation increases, and all of them have lower concentrations than the reference ratio. This fact corroborates the study conducted by Mattana et al (2012), in which the authors concluded that there is an almost linear tendency between workability and incorporated air concentration, where mortars with lower concentrations also have lower levels of workability. The results obtained for treated fibers are consistent with the theory obtained in the study of these authors.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Mortars with treated fibers exhibit a gradual decrease in the air incorporated concentration as the fiber incorporation increases, and all of them have lower concentrations than the reference ratio. This fact corroborates the study conducted by Mattana et al (2012), in which the authors concluded that there is an almost linear tendency between workability and incorporated air concentration, where mortars with lower concentrations also have lower levels of workability. The results obtained for treated fibers are consistent with the theory obtained in the study of these authors.…”
Section: Resultssupporting
confidence: 91%
“…These authors highlighted the importance of NaOH treatments in pineapple fibers, which after treatment began to show higher adhesions with the matrix, which caused a reduction in the incorporated air concentrations for mortars with fibers treated in NaOH solution. On the reference values, Mattana et al (2012) highlighted that mortars should have the incorporated air concentration limited to 20%, while Gomes & Neves (2002) suggest that the incorporated air concentration should be within the range between 8 and 17%. Taking these values as reference, all mortars under study have good behavior with respect to the properties of air incorporated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Analytical Hierarchic Process, AHP, is one of the multi-criteria analysis methodologies that assists the decision making in several fields of human knowledge. In civil engineering, the potential of AHP has been little explored, however it is possible to mention examples of studies that have used this tool as a decision making tool, such as: Marchezetti et al (2011), in the treatment of household waste; Lai et al (2008), in public works projects; Costa and Correa (2010), in post-occupation evaluation of buildings; Pereira, Medeiros and Levy (2012) and Mattana et al (2012) in studies on recycling of construction waste for the manufacture of concrete and mortar. According to Costa (2002) the method proposed by Saaty in the early 70s (Saaty, 1978), can be classified as one of the most known and used methods of multi-criteria analysis, aiming at the selection/choice of alternatives in a process that considers different evaluation criteria.…”
Section: Theory Of Hierarchical Analysismentioning
confidence: 99%
“…Argamassas são materiais de construção confeccionados a partir da mistura de aglomerantes (usualmente cimento Portland e cal hidratada), agregado miúdo e água, podendo ou não conter aditivos e adições químicas e minerais (CARASEK, 2017;MATTANA et al, 2012;NBR 13281, ABNT, 2005). A argamassa utilizada no presente estudo é classificada como argamassa de múltiplo uso.Essas argamassas podem desempenhar duas funções, assentamento de blocos ou revestimento de paredes e tetos.…”
Section: Introductionunclassified